Direct social work practice : theory and skills - Hepworth, Dean H.; Hepworth, Dean H. (Brooks/Cole empowerment series, 2013)
Packed with examples, illustrations, and learning experiences from the field of Social Work Practice, this title prepares social work students for effective real-world practice. It integrates the core competencies and recommended practice behaviors outlined in the "2008 Educational Policy and Accreditation Standards (EPAS)" set